Paradigm Shift: From Ownership Issues to Political Mediatization - Finsensius Yuli Purnama (Universitas Muhammadiyah Yogyakarta, 2022)
The political economy approach that focuses primarily on ownership issues has reached a saturation point and, at the same time, has some limitations. It could not explain the shift that occurred in the democratization process in Indonesia regarding the use of social media in Indonesia. Therefore, this paper offers a political mediatization paradigm in the relationship between media and democracy in the 2019 Presidential Election and the democratic trend in the 1955–2019 elections. This research suggests a map of media usage and the tendency of democracy in Indonesia’s 1955 - 2019 General Election and four quadrants of media and political mediatization with two main axes. The first axis has two poles: the media that promote democracy and the media that undermine democracy, and the second axis with the poles of politicizing media and political mediatization. The first quadrant is media that promotes democracy, and there is the mediatization of politics. The second quadrant is media that promotes democracy, and political media is politicized. The third quadrant is the mediatization of politics and media that undermines democracy. The last quadrant shows the politicization of media and media that undermine democracy.